Promoting Inclusion in Classroom Through Cooperative Instructional Techniques - Niure, Dhruba Prasad; Sapkota , Madhabi; Upadhyaya, Indra Raj (Pragya Darshan प्रज्ञा दर्शन, 2025)
This article investigates the effectiveness of various cooperative instructional techniques for promoting the inclusion of girls, marginalized, and disadvantaged children in secondary education in Nepal. The study used interpretivist paradigm followed by basic qualitative research, gathering information through focus group discussions, participant observation, and document analysis in a Nepali public school especially with grades 9-10 students. Four FGDs comprising of girls, marginalized, and disadvantaged students were conducted to gather qualitative information for the study. Furthermore, more than 20 conjugative lessons in social studies were conducted by using various instructional techniques. Then required information was collected, edited, transcribed, and analyzed by using various verbatim shared by informants. Study results showed that cooperative instruction methods were effective to cultivate interdependence, active engagement, we feeling, and inclusivity by empowering all students, including girls, marginalized, and disadvantaged to contribute and gain confidence. They were also useful to support and strengthen peer relationships, value diverse perspectives of students, foster social interaction and a sense of belonging, which ultimately improve learning students by breaking down social barriers.